Analytical approaches to the diagnosis and treatment of aging and aging-related disease: redox status and proteomics. (May 2015) - Calabrese, V.; Dattilo, S.; Petralia, A.; Parenti, R.; Pennisi, M.; Koverech, G.; Calabrese, V.; Graziano, A.; Monte, I.; Maiolino, L.; Ferreri, T.; Calabrese, E. J.
Abstract Basal levels of oxidants are indispensible for redox signaling to produce adaptive cellular responses such as vitagenes linked to cell survival; however, at higher levels, they are detrimental to cells, contributing to aging and to the pathogenesis of numerous age-related diseases. Aging is a complex systemic process and the major gap in aging research reminds the insufficient knowledge about pathways shifting from normal "healthy" aging to disease-associated pathological aging. The major complication of normal "healthy" aging is in fact the increasing risk of age-related diseases such as cardiovascular diseases, diabetes mellitus, and neurodegenerative pathologies that can adversely affect the quality of life in general, with enhanced incidences of comorbidities and mortality. In this context, global "omics" approaches may help to dissect and fully study the cellular and molecular mechanisms of aging and age-associated processes. The proteome, being more close to the phenotype than the transcriptome and more stable than the metabolome, represents the most promising "omics" field in aging research. In the present study, we exploit recent advances in the redox biology of aging and discuss the potential of proteomics approaches as innovative tools for monitoring at the proteome level the extent of protein oxidative insult and related modifications with the identification of targeted proteins.